Pengaruh Modifikasi Color Paper dan Multiball Terhadap Push dan Chop Forehand Tenis Meja - Andestiaji, Salsabila; Safari, Indra; Supriyadi, Tedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to apply a treatment with color paper and multiball modifications to the push and chop forehand table tennis. The study uses a quantitative approach to the design of the experiment, in which 22 pupils participated. Average percentage value of N-Gain 83%>76% This means that the practice given can be described as effective. And for the N-Gain score 0,83>0,7 Which means that the treatment given can be said to have achieved “high” effectiveness. From the test results above the mean value of color paper modification and multiball pretest 15,09 and 13,36, posttest values 22,36 and 16,36. Whereas seen from the P Value (0.010)>a (0,05) then the hypothesis is accepted. Conclusion, this study can state that color paper modifications have a greater influence on push and chop forehand. Keywords: Color paper, Forehand, Multiball